Muslim women in the United Kingdom and beyond - Benn, Tansin; Jawad, H. A. (Women and gender, the Middle East and the Islamic world ;, 2003)
Annotation The book explores ways in which Muslim women are portrayed, alongside their experiences of being Muslim and part of a predominantly western culture. It engages with Muslim women living predominantly in the United Kingdom, with contributions from other countries such as Australia, America and Sweden. Religious prejudice is a major theme that permeates the book, providing empirical evidence of ways in which islamophobia and visible symbols, such as the hijab, influence life experiences and perceptions of Muslim women negatively. Accounts of the impact of discrimination on life chances and opportunities are vivid. The book recounts ways in which the women cope in challenging diasporic contexts and concludes with recommendations for positive change. The text will be particularly valuable to anyone interested in issues of gender, religion and ethnicity, including students, employers, politicians and professionals.